Hearing Health Outcomes as a Function of Age, Gender, and Diversity - Joseph, Antony R. (Seminars in Hearing, 2022)
The United States does not ensure equitable access to hearing health care for all age groups, largely because these services are costly and even unobtainable in some places. Barriers to care are discussed within a context of the social determinants of health, under-representativeness of hearing-care professionals from historically marginalized communities, older adults and age-related hearing loss, and associated health conditions. The MarkeTrak 2022 study generated a sample of 15,138 respondents with information on 43,597 individuals. Data analysis revealed that self-reported hearing difficulty appears to increase with age with a rate of 12.4% for adults 18 years of age and older. A substantial proportion of individuals with hearing difficulty assumed that their problem was age-related, followed by exposure to loud sound and noise. Individuals with hearing difficulty were nearly three to four times more likely to have tinnitus, cognitive problems, and issues with balance and falling than those with no hearing problems. Self-reported hearing difficulty was lower for historically marginalized groups (7%) than for the White population (12%). Recommendations are presented to reduce the burden of hearing difficulty and hearing aid deserts for rural and urban populations.
Keywords: social determinants of health; barriers to care; marginalized communities; comorbidities; age-related hearing loss; hearing aid desert